Determinants of Rental Value in Telecommunication Towers: A Case Study from Gampaha District of Sri Lanka - Hathurusinghe, P.S.; Wickramaarachchi, N.C. (My University, 2015)
Real properties located within a ratable area are subjected to rating by the local authorities. Among the other types of properties the Telecommunication Towers are one of the important hereditaments which have increased in a significant number in the recent past in Sri Lanka. The system of property assessment tax for Residential, Commercial, Agricultural and the other types of properties are well established in the country. There is no proper practice to calculate the annual value of a tower and at present the contractors’ method is applying. The rule that where good rental is available, the other method of valuation must not be considered (case of GartonVs Hunter).This paper aims to analyze the determinants of the rental value, currently paid to towers in order to derive a better approach. In addition to the data gathered from Rating cards and Building applications, a structured questionnaire was conducted with the Service Providers of 74 towers in Gampaha District, was used for the analysis. Access to tower , terrain height from mean sea level, distance to neighborhood, distance to city, distance to public institutions (schools and hospitals), number of channels, land value, tower height, age of the tower, public objections and population density were treated as independent variables. The correlation results reveal that there is a positive correlation between the ground rental value and the value of the land plot (+.621), population density (+.403) and the access to tower (+.462). The distance from the city center, the tower height and Distance from Hospital indicates a negative impact (-0.323), (-0.503) and (-0.243) on the ground rental value. Analysis reveal that in estimating the rental value the positively correlated factors should be given a higher weight and the rental value based method can be applied to telecommunication towers for rating purpose.
Keywords: Valuation for rating; Property assessment; Telecommunication towers; Sri Lanka